An analysis of causes of poor attitude to work - Abang Ekhsan, Abang Othman; Wasilu, Suleiman (Elsevier Ltd., 2013)
The purpose of this paper is to examine the causes of poor attitude to work. The past decades have been characterized by unpredictable fluctuations in workers poor attitude. Organizations are faced with poor level of attitudes such as Erratic provision of services has become an increasing persistent problem facing the corporation and seriously affecting the general public, Careless and casual handling of the existing tools and machines and General nonchalant attitude of staff in the discharge of their duties. What are the causes? This crucial and yet unresolved questions has been and is still a source of concern to the owners, customers and members of the community as a whole and is critical for continuous research. Correspondingly, the review of the literature signifies a momentous shortage in this area of research. This study will empirically analyse the causes of poor attitude to work and is enriched by mixed methods such as questionnaire surveys and indepth interviews with respondents from various sectors. An aggregate of 70 questionnaires were analyzed. Furthermore, interviews with 11 staff were conducted. Poor attitude to work has a negative impact on productivity level of the organizations in Malaysia. Some of the prominent findings revealed that Malaysian workers widely held view that Poor Motivation, Inadequate Training and Development and Job Insecurity are the possible causes of poor attitude to work. The findings may not claim to be exhaustive and conclusive, in view of other contextual and external factors that might not have been addressed. Nevertheless, an organization cannot prosper well, succeed, grow or even survive without adequately addressing the issue of poor attitude. This paper provides some insights and practical implications to management of corporations, as a matter of priority to formulate intervention and policies to that effect.